The plastidial retrograde signal methyl erythritol cyclopyrophosphate is a regulator of salicylic acid and jasmonic acid crosstalk. (4th January 2016) - Lemos, Mark; Xiao, Yanmei; Bjornson, Marta; Wang, Jin-zheng; Hicks, Derrick; Souza, Amancio de; Wang, Chang-Quan; Yang, Panyu; Ma, Shisong; Dinesh-Kumar, Savithramma; Dehesh, Katayoon
Highlight: 2-C-Methyl-D -erythritol cyclopyrophosphate is an isoprenoid intermediate and a dynamic plastidial stress-specific signal that calibrates salicylic acid–jasmonic acid crosstalk and induces jasmonic acid-responsive genes in the presence of high salicylic acid in a manner dependent on the F-box protein COI1. Abstract: The exquisite harmony between hormones and their corresponding signaling pathways is central to prioritizing plant responses to simultaneous and/or successive environmental trepidations. The crosstalk between jasmonic acid (JA) and salicylic acid (SA) is an established effective mechanism that optimizes and tailors plant adaptive responses. However, the underlying regulatory modules of this crosstalk are largely unknown. Global transcriptomic analyses of mutant plants ( ceh1 ) with elevated levels of the stress-induced plastidial retrograde signaling metabolite 2-C-methyl-D-erythritol cyclopyrophosphate (MEcPP) revealed robustly induced JA marker genes, expected to be suppressed by the presence of constitutively high SA levels in the mutant background. Analyses of a range of genotypes with varying SA and MEcPP levels established the selective role of MEcPP-mediated signal(s) in induction of JA-responsive genes in the presence of elevated SA. Metabolic profiling revealed the presence of high levels of the JA precursor 12-oxo-phytodienoic acid (OPDA), but near wild type levels of JA in the ceh1 mutant plants. Analyses of coronatine-insensitive 1 ( coi1 )/ ceh1 double mutant plants confirmed that the MEcPP-mediated induction is JA receptor COI1 dependent, potentially through elevated OPDA. These findings identify MEcPP as a previously unrecognized central regulatory module that induces JA-responsive genes in the presence of high SA, thereby staging a multifaceted plant response within the environmental context.